(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The concept of “intersectionality” defines the analytical perspective in which markers of gender, race and class are considered inseparable pillars of oppression. Historically, poor black women are particularly affected in the most diverse daily situations, so that in 2009, 7.4% of black women found themselves in a situation of extreme poverty, representing the highest percentage. This statement highlights the interrelationship proposed by intersectionality and the importance of analyzing this context in the legal sphere, as it highlights the relationship between these pillars and how they affect these women. Considering that criminal law is committed to protecting criminally relevant legal assets such as life, property, sexual dignity, and other assets of those individuals inserted in society, this article seeks to identify whether intersectionality interferes negatively in the protection legal status of this collective. The approach used consisted of the deductive method, through analysis and bibliographic review of works related to this topic, in addition to the analysis of research related to the topic. It was concluded that the protection of relevant legal assets is not carried out in a democratic manner in practical terms. It was observed that in the criminal sphere, poor black women are treated disrespectfully and become victims of neglect and invisibility. The research revealed that, despite fundamental developments in criminal legislation, criminal justice is lethargic when it comes to implementing legal protection for poor black women, demanding reform that prioritizes effectiveness and equality in the protection of such victims.